Microstructural changes of young cement paste due to moisture transfer at low air pressures. (February 2023) - Zuo, Shenghao; Yuan, Qiang; Huang, Tingjie; Zhang, Kai; Shi, Jinyan; Tan, Yanbin
Abstract: It has been long recognized that low air pressure (AP) affects the moisture transfer in concrete, and thus its microstructure and bulk property, but less is known about the thermodynamic mechanism. This research investigated the microstructure evolution of young white Portland cement paste during wetting or drying at different APs (i.e. 101 kPa, 60 kPa, 20 kPa), the experimental and numerical analyses reveal the moisture transfer changes at low APs, which matters for the microstructural features of hardened cement paste. It was found that low APs increase the water vapor diffusion and convective mass transfer coefficients, and the intrinsic permeability of cement paste sample, which results in higher water contents within cement paste during wetting at 98 % RH but more rapid water losses during drying at 43 % RH. Owing to the distinct moisture transfer behaviors, the C-S-H structures were linked with water contents within confined pores.